DESKRIPSI TENTANG PESERTA DIDIK YANG MEMILIKI KEPRIBADIAN INTROVERT KELAS X SMA NEGERI 5 PONTIANAK - Hasanah, Ulfatul; Purwanti, Purwanti; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIntrovert individual personality does not have much experience in the outside world but has a broad and deep thinking on the outside world. Introvert personality has a negative impact on social activities, but also has a positive impact. Therefore learners are expected to be more able to bring themselves in the social environment both in school and the outside world. The method used is a descriptive method and form of research survey. The Samples of this research is 49 students. This research uses quantitative research. The techniques of data collection are questioner and interview. The technique of Data analysis is the percentage formula. Based on the results from data analysis of a descriptive research the Introvert personality achieve the score on the category